Factors Affecting Work Motivation of Insurance Agents (Case Study At PT. Sun Life Financial Unit Syariah Medan City - Anysa Putri; Rahmi Syahriza (Journal of Indonesian Management, 2022)
This study aims to find out what are the main factors of work motivation of insurance agents. Insurance companies that are sometimes still underestimated by others, may be the most promising and productive job opportunities today. Certain births and deaths make insurance very suitable as a long-term investment for the family. In carrying out their duties, insurance agents are responsible for marketing and selling insurance services to cover losses caused by illness, car accidents, fires, earthquakes, and so on. In addition, the insurance agent serves as an intermediary for an agreement between the insured and the insurer which will later be regulated in the insurance agreement. This study uses observational research methods and literature studies and researchers find that agents have a great influence on the success of insurance companies for many years. Therefore, according to researchers, the work motivation of agents is an interesting topic to discuss.